PROGRESSIVE WEB APPS UNTUK REKAYASA HYBRID APPLICATION BERBASIS TEKNOLOGI MEAN STACK - Rusdy Agustaf; Bernard Renaldy Suteja (Informasi Interaktif, 2019)
The main obstacle in making a mobile app is the variety of platforms and operating system versions of mobile devices, as a result the application must be adjusted accordingly. In a long period of time web programming techniques have developed into progressive web apps that can be used for hybrid apps. Hybrid application is an application that can run on many platforms. MEAN Stack technology can be used to produce a good hybrid app. The Ionic framework can be used to implement MEAN Stack technology to produce a hybrid app that is easy and stable. Keywords : Progressive Web Apps, Hybrid Application, MEAN stack